The Effect of Inquiry Laboratory with Group Discussions Method on Improving of Students’ Learning Outcomes - Maulina, Dina; Hernawati, Diana; Rakhmawati, Ismi; Lengkana, Dewi; Fauzisar, Ave Suakanila (Jurnal Pendidikan MIPA, 2019)
This study aims to determine the effect of laboratory-based inquiry learning models with group discussion methods in improving student learning outcomes. The research subjects were students of the 2012/2013 biology education who took the vertebrate zoology course. The sample used in this study was taken using a cluster random sampling technique of 2 classes. The concept discovery observation data in the form of quantitative data obtained through cognitive test sheets consisting of 25 questions and tested using the t test with a real level α = 0.05. Based on the results of data analysis shows that there is an influence of laboratory-based inquiry learning models on diversity of vertebrate animals.Keywords: laboratory learning, student learning outcomes, inquiry. DOI: http://dx.doi.org/10.23960/jpmipa/v20i1.pp1-6